Analisis Wacana Humor Dalam Ceramah Gus Baha’ - Bambang Hariyanto (Dialektika: Jurnal Bahasa, Sastra, dan Pendidikan Bahasa dan Sastra Indonesia, 2022)
Humor is part of human daily activities and it is an effective method to reduce tension and stress in a person. The humor strategy is an effective method of preaching in order to attract the interest of the congregation. This paper is to describe and fill the gaps of the humorous lecture method delivered by the preacher. Gus Baha' has become a phenomenal preacher and a source of pride for traditionalist Islam or Nhadliyin (NU) which currently dominates the Islamic discourse in Indonesia. This study uses a qualitative descriptive approach by utilizing the transcription of Gus Baha's video lectures on YouTube. The illocutionary speech act theory from Searle (1979) was used to describe the utterances in his lectures and to utilize the discourse register from Agha (2007) in analyzing the data. The results of the study found forms of using humorous communication strategies in presenting religious lectures. The forms of special terms in his humorous speeches become a typical strategy to attract the congregation.